2003
DOI: 10.1021/ol035332y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an Oxazoline Analogue of Apratoxin A

Abstract: [structure: see text] Michael addition of Me(2)Cu(CN)Li(2) to alpha,beta-unsaturated lactone 7 derived from beta-hydroxyl ketone 5 provides lactone 8, which is converted to alcohol 11 using Oppolzer's methodology as the key step. Connection of 11 with the l-proline moiety and subsequent installation of an oxazoline ring affords 16, which is coupled with tripeptide 21; subsequent macrocyclization then furnishes 4, an oxazoline analogue of apratoxin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Wipf and Uto elegantly demonstrated that the oxazoline moiety was ringopened to the corresponding thioamide on a cyclic peptide by treatment with H 2 S, and then dehydrative cyclization using N,N-dimethylaminosulfur trifluoride (DAST) led to the total synthesis of the thiazoline-containing cyclic peptide trunkamide A. 13) We initially synthesized the oxazoline analogue of apratoxin A (16) 7,14,15) and attempted to convert the oxazoline moiety to a thiazoline ring. triazol-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HATU)/N,N-diisopropylethylamine (DIEA)), gave undesired azlactone 10 in 49% yield, along with the desired tetrapeptide 9 in only 21% yield.…”
Section: Apratoxin Amentioning
confidence: 99%
“…Wipf and Uto elegantly demonstrated that the oxazoline moiety was ringopened to the corresponding thioamide on a cyclic peptide by treatment with H 2 S, and then dehydrative cyclization using N,N-dimethylaminosulfur trifluoride (DAST) led to the total synthesis of the thiazoline-containing cyclic peptide trunkamide A. 13) We initially synthesized the oxazoline analogue of apratoxin A (16) 7,14,15) and attempted to convert the oxazoline moiety to a thiazoline ring. triazol-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HATU)/N,N-diisopropylethylamine (DIEA)), gave undesired azlactone 10 in 49% yield, along with the desired tetrapeptide 9 in only 21% yield.…”
Section: Apratoxin Amentioning
confidence: 99%
“…Due to the structural novelty, coupled with the exceptional biological activity of apratoxin A, several synthetic research groups carried out total synthesis of 67 and its analogues (73-76) (Fig. 8) for the purpose of SAR studies (Chen and Forsyth 2003a;b;Chen and Forsyth 2004;Zou et al 2003;Doi et al, 2006;Ma et al 2006;Numajiri et al 2009;Gilles et al 2009). An oxazoline analogue of apratoxin A, oxapratoxin A (73), was found to be slightly lower in potency against HeLa cells when compared with apratoxin A (Table 2; Ma et al 2006).…”
Section: Apratoxins and Analoguesmentioning
confidence: 99%
“…Chemical synthesis may complement this potential by offering an expedient route to structurally diversify the apratoxin chemotype. Accordingly, a few studies related to the chemical synthesis of the apratoxins have been published (19,20), including the synthesis an oxazoline-containing analog (21). A complete total synthesis can also address the immediate apratoxin supply limitation and corroborate the assigned structures of the natural products.…”
mentioning
confidence: 99%